Determinants of Consumer Perception and Adoption Intentions towards Solar Energy Products: An Empirical Study in Madurai District (International Journal of Food and Nutritional Sciences, 2023)
As India moves toward its net-zero goals, regional adoption of renewable energy becomes critical. This study investigates consumer perception toward solar energy products in the Madurai district of Tamil Nadu. Using a descriptive research design, primary data was collected from 300 respondents via structured questionnaires. The study examines awareness levels, perceived benefits, and barriers to adoption. Results indicate that while environmental consciousness and government subsidies (e.g., PM Surya Ghar Muft Bijli Yojana) drive positive perception, high initial costs and lack of technical knowledge remain significant hurdles. Statistical analysis reveals a significant correlation between education levels and the adoption of solar rooftop systems. The paper concludes with strategic recommendations for policymakers to enhance solar penetration in Madurai district.